Who pays the property tax? Evidence from Brazil. (September 2022) - Carvalho Junior, P.H.B.; De Cesare, C.
Abstract: Using Brazil's Survey of Household Budget (POF) 2017–2018, this study develops a logit model to identify the social groups and their property features that are less likely to pay Urban Property Tax (UPT). The data shows that frequency of UPT payments among urban owner-occupied properties has increased from 36.1% to 56.1% over 15 years (comparing POF 2002–2003 and POF 2017–2018). The logit model reveals that property attributes (regional location, state capital location, and the availability of urban services) were the main determinants of UPT payment. Houses located in Northern Regions were 62.9% less likely of UPT payment, while houses locate in state capitals were 48.0% less likely. Houses benefited of only three typical urban services were 45.4% less likely comparing to houses with five urban services. In addition, households where the head of families are woman, non-white, self-employed or not working, with concern of food shortage, with more children and fewer years of study were also less likely of UPT payment than others. The study concludes that marginalization and regional specificities were the main determinants of UPT payment propensity and recommends tax policies to ensure more progressivity and to reduce regional disparities. Highlights: The rate of property tax payment among urban households in Brazil increased from 36.1% to 56.1% between 2002 and 2018. Houses in Northern regions, large cities, or benefited of fewer urban services are less likely to pay property tax. Individuals who are women, non-whites, less educated, self-employed, or with more children are less likely to pay property tax. There is a need of property tax policies with a more progressive bias, target on poor families.